2019
DOI: 10.4103/jlp.jlp_16_19
|View full text |Cite
|
Sign up to set email alerts
|

Castleman's disease associated with calcifying fibrous tumor: A rare association with review of literature

Abstract: Castleman's disease is a rare disease characterized by unicentric or multicentric enlargement of the lymph node, and it is mostly of the hyaline vascular type. Calcifying fibrous tumor is a neoplasm characterized by large areas of hyalinized collagen with paucicellular areas along with dystrophic calcification and scattered lymphoplasmacytic infiltrates. There are only five case reports to describe an association between these two entities. We report a case of a 38-year-old male with seropositivity for hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 3 4 5 6 7 8 9 10 11 Its etiology is still undetermined, although an association with IgG4-related diseases, such as Castelman's disease, has been suggested. 12 With varying location, the tumor typically presents embedded into its regional structures. Histologically with abundant dense collagenous tissue in whorled arrangements with low cellularity, identifiable by its psammomatous calcification and lymphoplasmacytic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 5 6 7 8 9 10 11 Its etiology is still undetermined, although an association with IgG4-related diseases, such as Castelman's disease, has been suggested. 12 With varying location, the tumor typically presents embedded into its regional structures. Histologically with abundant dense collagenous tissue in whorled arrangements with low cellularity, identifiable by its psammomatous calcification and lymphoplasmacytic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this association remains unclear and raises the possibility that both entities may represent different stages of the same reactive disease process. It has been suggested that CFT-like features in lymph nodes of patients with hyaline vascular type Castleman disease are the result of fine needle aspiration-induced trauma, supporting the notion that CFTs may be reactive proliferations resulting from trauma[ 21 , 22 ]. Further supporting this theory are reports of patients developing soft tissue CFTs within a few months of sustaining trauma at the same anatomic site[ 27 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…The hyaline vascular type is characterized by germinal centers surrounded by concentric rings of mantle zone lymphocytes and a hyalinized vascular proliferation between follicles[ 20 ]. Six cases have been reported from 1999 to 2019 in which CFT was found in association with hyaline vascular type Castleman disease[ 21 - 26 ]. In some cases, both CFT and hyaline vascular type Castleman disease were found to co-exist within the same lymph node tissue[ 21 , 22 , 25 , 26 ], while in other cases, patients with gastrointestinal CFTs were found to have hyaline vascular type Castleman disease in adjacent lymph nodes[ 23 , 24 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation